Responsibility of Land Deed Officials for False Information on The Selling Buying Deed (Case Study Court Decision No Number 66/PDT.G/2016/PN TSM) - Vanessa Angelina; Mohamad Fajri Mekka (LEGAL BRIEF, 2022)
There is a lawsuit starts from the debt of the seller to the buyer of IDR 720,000,000 (seven hundred and twenty million Rupiah). From the proceeds of the debt, the seller guarantees the land to the bank under the name of the buyer, with the sole purpose of returning the land when in is paid off. Over time the land was not returned and the seller filed a lawsuit against the buyer. The official who made the land deed who made the Sale and Puchese Deed also become a Co-Defendadnt to be held accountable for the Sale and Purchase Deed Number 401/2012 dated August 8, 2012. To answer this problem, the author uses the normative juridical method. From the results of this study, it shows that the official making the land deed in making the Sale and Puchase Deed has done it legally and is not responsible for the false information. the official making the land deed is only responsible for formal and material data and applies the precautionary principle.